Antibody markup language (AbML) - a notation language for antibody-based drug formats and software for creating and rendering AbML (abYdraw) - James Sweet-Jones; Maham Ahmad; Andrew C.R. Martin (Taylor & Francis Group, 2022)
As interest in antibody-based drug development continues to increase, the biopharmaceutical industry has begun to focus on complex multi-specific antibodies (MsAbs) as an up-and-coming class of biologic that differ from natural monoclonal antibodies through their ability to bind to more than one type of antigen. As techniques to generate such molecules have diversified, so have their formats and the need for standard notation. Previous efforts to develop a notation language for macromolecule drugs have been insufficient, or too complex, for MsAbs. Here, we present Antibody Markup Language (AbML), a new notation language specifically for antibody formats that overcomes the limitations of existing languages and can annotate all current antibody formats, including fusions, fragments, standard antibodies and MsAbs, as well as all currently conceivable future formats. AbML V1.1 also provides explicit support for T-cell receptor domains. To assist users of this language we have also developed a tool, abYdraw, that can draw antibody schematics from AbML strings or generate an AbML string from a drawn antibody schematic. AbML has the potential to become a standardized notation for describing new MsAb formats entering clinical trials.Abbreviations: AbML: Antibody Markup Language; ADC: Antibody-drug conjugate; CAS: Chemical Abstracts Service; CH: Constant heavy; CL: Constant light; Fv: Variable fragment; HELM: Hierarchical Editing Language for Macromolecules; HSA: Human serum albumin; INN: International Nonproprietary Names; KIH: Knobs-into-holes; mAbs: Monoclonal antibodies; MsAb: Multi-specific antibody; WHO: World Health Organization; PEG: Poly-ethylene glycol; scFv: Single-chain variable fragment; SMILES: Simplified Molecular-Input Line-Entry System; VH: Variable heavy; VHH: Single-domain (Camelid) variable heavy; VL: Variable light